Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Kerja Karyawan CV. Citra Proteksindo Kota Jambi - Mustika Mustika; Muhammad Amali (Ekonomis: Journal of Economics and Business, 2020)
This research aims to find out how much motivation and work experience influence on employee productivity, the population in this study is all employees on cv. Citra Proteksindo Jambi City. Data analysis using multiple linear regression analysis, T test, F test, R². The results of the study show that Motivation and Work experience simultaneously affect employee productivity, and partially motivation has no effect on employee productivity while work experience affects employee productivity.